Trilobite-based biostratigraphic model (biofacies and biozonation) for the Middle Cambrian carbonate platform of the Argentine Precordillera - O.L. BORDONARO; A.L. BANCHIG; B. PRATT; M.M. RAVIOLO (Geologica Acta, 2009)
A preliminary biostratigraphic model that combines trilobite biofacies and biozonation is proposed for the early Marjumian (Middle Cambrian) of the Precordillera of western Argentina. This interval involves a variety of paleogeographic–paleoenvironmental settings across the carbonate platform, ranging from its interior to exterior areas beyond the platform margin and including both open-marine and near-shore environments. This model is based on three stratigraphic sections of the basal part of the Alojamiento Formation, which crops out in the Cordón del Alojamiento (Provincia de Mendoza) and Cordón de Santa Clara (Provincia de San Juan); and three sections of the Soldano Member of La Laja Formation in the Sierra Chica de Zonda (Provincia de San Juan). Three biofacies were recognized on the basis of trilobite associations that show a marked environmental distribution: 1) The Ptychagnostidae Biofacies is represented by an assemblage exclusively dominated by agnostoids, most of them belonging to Ptychagnostus; this assemblage occurs in mudstones and calcareous shales deposited below storm wave-base seaward of the platform margin; 2) the Peronopsidae Biofacies also developed in the external areas but it occurs in limestones deposited between fair-weather and storm wave-base; this assemblage is likewise dominated by agnostoids, but instead belonging to Peronopsis, with the rest of the fauna comprising polymeroids (Dolichometopidae, Oryctocephalidae, Zacanthoididae and Alokistocaridae); 3) the Alokistocaridae Biofacies occurs in grainstones, mudstones and calcareous shales deposited between fair-weather and storm wave-base under changeable conditions located near the platform margin and in the interior. It is dominated by alokistocarids whose relative abundance increases landward from 52% to 58% and to 95%. The remaining components belong to Dorypygidae, Zacanthoididae and Oryctocephalidae; Eodiscidae and Peronopsidae comprise minor proportions in the most seaward location. Due to the contrasting, environmentally mediated associations, these sections belong to three essentially synchronous biozones erected previously for the Middle Cambrian of western Laurentia, the Ptychagnostus gibbus, Oryctocephalus and Ehmaniella Biozones.